PERSEPSI STAKEHOLDERS TERHADAP TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI DI KABUPATEN LOMBOK TENGAH - ishaq ishaq (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This study aimed to analyze the differences in perception between internal stakeholders with external stakeholders to transparency and accountability in financial management of the school. The population in this study were all teachers, staff, administrators of the school committee who becomes the object of research, vocational superintendent, Board of Education Central Lombok, and Non-Governmental Peoples, which operates in the field of education. The object of this study is SMKN 1 Central Praya, SMK 1 Praya, SMK 1 Kopang, SMK 1 Pujut, SMK 1 Janapria, SMK 1 Batukliang, SMK 1 North Batukliang, SMK 1 West Praya, and SMK 2 Central Praya. This research is descriptive quantitative research with a sample of 227 people. Statistic analysis results show: 1) the difference in the average perception of internal and external stakeholders on the transparency of financial management SMK in Central Lombok regency; 2) There is no difference in the average perception of stakeholders internal and external to the SMK accountability in financial management in Central Lombok regency.          Keywords : Stakeholders Perception, Transparency, Accountability, Financial Management Schools